Comparison of morphogenesis and anatomy between hairy roots and adventitious roots of Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) - Huong, Trinh Thi; Linh, Nguyen Thi Nhat; Tung, Hoang Thanh; Hien, Vu Thi; Luan, Vu Quoc; Manh Cuong, Do; Tuan, Tran Trong; Ngoc, Pham Bich; Ha, Chu Hoang; Quang Duc Tien, Nguyen; et al. (Vietnam Journal of Biotechnology, 2020)
In this study, morphogenesis and anatomy of adventitious roots and hairy roots of Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) were compared. Adventitious roots were derived from four different samples (leaf, petiole, root and callus) in vitro cultured on medium SH supplemented with 5 mg/L IBA. Hairy roots were derived from callus infected with Agrobacterium rhizogenes strain ATCC 15834. The results showed that there were significant differences in morphogenesis and anatomy, the pathway of secondary roots formation, culture medium between adventitous roots and hairy roots. The hairy roots strongly grew and branched on the free-plant growth regulator medium. The secondary root of the hairy root was formed in two pathways: (1) The secondary root formation began at the vesicles system of main root; (2) The secondary root formation was independent of the vesicles system of main root; it kept developing in length and connected to the vesicles system of main root. On the other hand, growing adventitous roots only grew on the environment with exogenous auxin supplementation; also their branching ability were low. The secondary root formation of the adventitous root was started at the vesicles of the main roots and there was only one secondary root that was formed at an location of adventitous root. The results that obtained in this study will be the reference to identify two types of root.